Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.9787/pbb.2016.4.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Temperature Regime to Screen Cold Tolerant Rice Seedlings

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. ABSTRACT Low temperature stress at the seedling stage of rice is an important factor causing the leaf discoloration, wilting and consequently leads to non-uniform crop maturation. In order to screen the cold t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The average temperature was close to the point where rice damage begins, at about 15 • C [34,35]. The germination and seedling growth rates of the cold-sensitive cultivars were low, as described in earlier studies [38,[46][47][48]. Therefore, this kind of long-term cold stress leads to greater differences among the genotypes than autumn screening (Figures 3 and 4).…”
Section: Discussionsupporting
confidence: 62%
“…The average temperature was close to the point where rice damage begins, at about 15 • C [34,35]. The germination and seedling growth rates of the cold-sensitive cultivars were low, as described in earlier studies [38,[46][47][48]. Therefore, this kind of long-term cold stress leads to greater differences among the genotypes than autumn screening (Figures 3 and 4).…”
Section: Discussionsupporting
confidence: 62%
“…Visual inspection reported more stable results when mixed with other methods [38]. Visual inspection by the SPAD method or measurement of chlorophyll or photosynthesis rate was more reliable than visual inspection alone [40].…”
Section: Discussionmentioning
confidence: 89%
“…However, since the experiential knowledge of the observer judges the visual measurement method, it is not an objective judgment. Nonetheless, low-temperature plant damage generally leads to changes in color [38], and these changes have been used as a critical indicator of cold tolerance [39]. The visual inspection showed that S. scilloides was more tolerant, followed by H. longipes, H. plantaginea, and H. fulva.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, cold sensitive genotypes had high proportion of saturated fatty acids than unsaturated fatty acids resulting in high transition temperature (Sudesh, 2010). IRRI ( 2013) developed a standard evaluation system (SES) scale to distinguish tolerant and susceptible rice genotypes, which has been used by several studies for cold tolerance evaluation (Andaya and Mackill, 2003;Kim and Tai, 2011;Hyun et al, 2016). Leaf growth/leaf wilting score is one of an essential measurement for cold stress damage.…”
Section: Performance Of Selected Rice Genotypes Across Environments F...mentioning
confidence: 99%